Implementasi Sistem Penunjang Keputusan Preferensi Siswa Terhadap Perguruan Tinggi Negeri (PTN) Perguruan Tinggi Swasta (PTS) atau Perguruan Tinggi Kedinasan (PTK) dengan Menggunakan Metode MFEP (Multifactor Evaluation Process ) Berbasis WEB (Studi Kasus: SMA Negeri 1 Ranto Baek) - Hanum, Luthfia; Arlis, Syafri; Marfalino, hari (Jurnal Teknik dan Teknologi Tepat Guna, 2024)
The design of a decision-making information system in determining student preference for state Universities (PTN), Private Universities (PTS), or Public Universities (PTK) using the WEB -based MFEP (Multifactir Evaluation Process) method aims to determine student preferences for universities based on the factors that have been provided, namely: Cost, Prestigious, Campus Accreditation, Study Program Accreditation, Job Opportunities and Location. The Utilization of the internet by creating a website with the help oh the PHP programming language and MySQL as data storage is expected to facilitate student in making decision.